2021
DOI: 10.3892/etm.2021.10093
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in HUVECs induced by microRNA‑616‑3p via X‑linked inhibitor of apoptosis protein targeting

Abstract: Atherosclerosis causes stroke and coronary heart disease and is associated with a high mortality rate worldwide. However, the pathogenesis of atherosclerosis remains unclear. Endothelial cell apoptosis is one of the early changes observed in atherosclerosis. Previous studies have found that microRNA (miR)-616-3p may be involved in the development of atherosclerosis, but the specific mechanism is not clear. The present study aimed to investigate whether miR-616-3p is involved in endothelial cell apoptosis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…However, our results show that miR-616 expression attenuates the Furthermore, we observed that expression of miR-616 was reduced in human breast cancers as compared to tumour adjacent normal tissue (Fig 9). In agreement with our results miR-616-3p has been shown to potentiate apoptosis in HUVECs (16), inhibit head and neck squamous cell carcinoma progression (17) and inhibit cell growth and mammosphere formation of breast cancer cells (18,25). Any small RNA having G-rich 6mer seed sequence (nt 2-7 of the guide strand) can reduce viability of cells when associated with RNA-induced silencing complex.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our results show that miR-616 expression attenuates the Furthermore, we observed that expression of miR-616 was reduced in human breast cancers as compared to tumour adjacent normal tissue (Fig 9). In agreement with our results miR-616-3p has been shown to potentiate apoptosis in HUVECs (16), inhibit head and neck squamous cell carcinoma progression (17) and inhibit cell growth and mammosphere formation of breast cancer cells (18,25). Any small RNA having G-rich 6mer seed sequence (nt 2-7 of the guide strand) can reduce viability of cells when associated with RNA-induced silencing complex.…”
Section: Discussionsupporting
confidence: 92%
“…MiR-616 targets tissue factor pathway inhibitor (TFPI-2) in prostate cancer (9); PTEN in HCC and gastric cancer (15); SOX7 in glioma and NSCLC (14). However, miR-616-3p has been reported to reduce XIAP expression and potentiate apoptosis in HUVECs (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor‐promoting impact of miR‐616‐3p had been reported in gastric cancer 17 and pancreatic cancer, 18 but it exerted an anti‐tumor impact on breast cancer 19 . Also, miR‐616‐3p could repress HUVEC proliferation and induce HUVEC apoptosis in atherosclerosis 20 . The former work showed that miR‐616‐3p could promote cell migration, growth and EMT via regulating tissue FPI‐2 in PE 21 .…”
Section: Introductionmentioning
confidence: 95%
“…19 Also, miR-616-3p could repress HUVEC proliferation and induce HUVEC apoptosis in atherosclerosis. 20 The former work showed that miR-616-3p could promote cell migration, growth and EMT via regulating tissue FPI-2 in PE. 21 However, the relationship between hsa_circ_0015382 and miR-616-3p in PE is unclear.…”
Section: Introductionmentioning
confidence: 99%